Actitudes hacia la lectura en estudiantes del sexto grado de primaria de la Institución Educativa N° 601491 Madre Teresa de Calcuta, distrito de San Juan Bautista en el año 2024 - Tapayuri Nuñez, Monica (2025)
Objective: To describing the attitudes toward reading of the sixth grade elementary school students of the educational institution N° 61004 Madre Teresa de Calcuta in the District of San Juan Bautista 2024. Method The present study is a non experimental study with a simple descriptive research design. The data collection technique used was estructured interview and its instrument was the questionnaire. The instrument was previously validated by expert judgment. The sample consisted of 135 students of the sixth grade elementary school students of the educational institution N° 61004 Madre Teresa de Calcuta. Results: The results was processed trough the absolute frequency table, relative frequencies table, average,and standart deviation. It was observedthat 93.3% have acceptance attitude towards reading and 6.7% have rejection attitude towards reading.Conclusion: It has been possible to determine that the attitudes toward the reading are acceptance attitude in the sixth grade elementary school students of the educational institution N° 61004 Madre Teresa de Calcuta.